2022
DOI: 10.3389/fphy.2021.806231
|View full text |Cite
|
Sign up to set email alerts
|

Compaction Density Evaluation Model of Sand-Gravel Dam Based on Elman Neural Network With Modified Particle Swarm Optimization

Abstract: The compaction density of sand-gravel materials has a strong gradation correlation, mainly affected by some material source parameters such as P5 content (material proportion with particle size greater than 5 mm), maximum particle size and curvature coefficient. When evaluating the compaction density of sand-gravel materials, the existing compaction density evaluation models have poor robustness and adaptability because they do not take into full consideration the impact of material source parameters. To overc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Since QC/QA of earthwork are closely related to compaction parameters and compaction quality, the research of digital rolling compaction methods mainly focuses on monitoring compaction parameters and compaction quality (see Figure 6 ). Combined with the cluster analysis results in Figure 1 , digital rolling compaction methods are the current research hotspot in the QC/QA methods of earthwork and have been widely used in the construction of roads [ 11 , 23 , 32 ], railways [ 34 , 95 ], airports [ 8 , 35 ], and dams [ 24 , 36 , 96 ].…”
Section: Digital Rolling Compaction Methodsmentioning
confidence: 99%
“…Since QC/QA of earthwork are closely related to compaction parameters and compaction quality, the research of digital rolling compaction methods mainly focuses on monitoring compaction parameters and compaction quality (see Figure 6 ). Combined with the cluster analysis results in Figure 1 , digital rolling compaction methods are the current research hotspot in the QC/QA methods of earthwork and have been widely used in the construction of roads [ 11 , 23 , 32 ], railways [ 34 , 95 ], airports [ 8 , 35 ], and dams [ 24 , 36 , 96 ].…”
Section: Digital Rolling Compaction Methodsmentioning
confidence: 99%
“…Each stage has several tasks. This approach helps to improve the reliability of the evaluation and the reliability of the evaluation results [22].…”
Section: The Shortcomings Of Traditional Physical Education Teaching ...mentioning
confidence: 99%
“…Subsequently, our research on the Qarqan River revealed that the new Dashimen Water Conservancy Hub Project, constructed upstream, offers comprehensive benefits such as flood control, power generation, irrigation, and water supply. This project has effectively alleviated the seasonal water shortage in the irrigation area and has significantly contributed to local economic and social development [38,39]. The project began lowering and storing water on 20 September 2021 and was first put into spring production in 2022; prior to storage, this area was essentially dry.…”
Section: Analysis Of the Causes Of Changes In Water Area Of Taitma Lakementioning
confidence: 99%